The aero-aquatic Helicodendron microsporum n. sp from Mallorca, Spain - Abdullah, S. K.; Cano, J.; Descals, E.; Guarro, J. (MYCOLOGICAL RESEARCH, 2000)
A new aero-aquatic helicosporous hyphomycete, Helicodendron microsporum, is described and illustrated from decaying leaves submerged in a small artificial pond surrounded by Quercus ilex and Pinus halepensis in Mallorca, Spain. It is characterized by branched conidiophores with chains of hyaline conidia eventually forming white clusters which do not break up even at maturity. It also has small conidia (8-10 mu m diam.) consisting of a 2-2.5 mu m thick filament which coils 1.5-2 times counter-clockwise. The main characters of the species are compared with 14 similar hyalosporous Helicodendron species.
APSAPSThe following values have no corresponding Zotero field: pub-location: 40 WEST 20TH STREET, NEW YORK, NY 10011-4211 USA publisher: CAMBRIDGE UNIV PRESS
Keywords: deaying leaves; hyphomycete; Pinus halepensis; Quercus ilex; Spain